The Compleat Angler - Walton, Izaak, 1593-1683 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Compleat Angler" by Izaak Walton is a book first published in 1653. Written in the aftermath of the English Civil War, it celebrates the art and spirit of fishing through prose and verse. The work presents scenes of harmony away from political turbulence, following Londoners on fishing trips through the English countryside. Beginning as a dialogue between veteran angler and student, the book grew through multiple editions over twenty-five years, ultimately expanding to include instruction in fly fishing. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Compleat_Angler
Release date is 1996-10-01
Produced by Tokuya Matsumoto
Keywords: Fishing -- Early works to 1800